CORRELATION OF MUFRODAT (VOCABULARY) MASTERY WITH ABILITY TO READ ARABIC TEXTS OF CLASS VIII STUDENTS SMP IT AL-FIKRI MAKASSAR - Abqar, Akhirul; Jufri, Jufri; Kudus, Ruhul (PT. Jurnal Center Indonesia Publisher, 2025)
This research is a correlation study using a quantitative approach that aims to find the correlation between Mufrodat Mastery (Vocabulary) and Arabic Text Reading Ability of Students in Grade VIII of IT Al-Fikri Junior High School Makassar. The independent variable in this study is Mufrodat Mastery (Vocabulary), while the dependent variable is Arabic Text Reading Ability. The population in this study were all students of grade VIII of IT Junior High School Al-Fikri Makassar which amounted to 50 students and the sample in this study were students of grade VIII which amounted to 20 students. The research data were obtained by giving written tests in the form of Arabic vocabulary mastery tests and Arabic text comprehension reading ability tests. The data analysis technique is inferential statistical analysis of bivariate correlation type with the result of correlation coefficient 0.578 and significance value 0.008. The results of this study indicate that there is a moderate positive correlation between Mufrodat Mastery (Vocabulary) and Arabic Text Reading Ability. Thus it can be concluded that there is a correlation between Mufrodat Mastery (Vocabulary) and Arabic Text Reading Ability of 8th Grade Students of IT Al-Fikri Junior High School Makassar.